A 60‐GHz on‐chip slot‐array antenna in integrated‐passive‐device technology for antenna‐in‐package applications. Issue 2 (2nd May 2013) - Biglarbegian, Behzad; Nezhad‐Ahmadi, Mohammad‐Reza; Enayati, Amin; Vandenbosch, Guy A. E.; De, Walter; Safavi‐Naeini, Safieddin
ABSTRACT A new millimeter‐wave antenna structure on a low‐cost, production platform integrated passive device technology is presented. The antenna consists of a 2‐by‐1 array of slot antennas at 60 GHz. An in‐house developed on‐chip antenna measurement setup was used to characterize the fabricated antenna. The measurement results show an antenna gain of more than 5 dBi with a return loss of 18 dB at 60 GHz. The better‐than‐10‐dB impedance bandwidth of the antenna covers the 60‐GHz unlicensed band from 57 to 64 GHz. The 3‐dB beamwidths of the antenna are 105° and 76° at E‐plane and H‐plane at 60 GHz, respectively. The size of the die of the antenna is 2 mm × 4.5 mm. © 2013 Wiley Periodicals, Inc. Int J RF and Microwave CAE 24:155–160, 2014.